A case study analysis : Sindora Berhad / Azizah Paiman … [et al.] - Paiman, Azizah (Faculty of Business and Management, 2002)
Our lecture. Prof Madya Kamel Taufiq b Abd Ghani has assigned us to carry out the case study of Sindora Berhad as a fiilfilment of the sublect of Strategic Management (MGT 585). Sindora Berhad was incorporated in Malaysia on 30 December 1972 under the Companies Act 1965. It was listed on the main Board of the Kuala Lumpur Stock Exchange on 7 December 1995 with paid up capital of RM 96 million. Today, after spinning over two decades, Sindora Berhad Group of Companies has successfully sustained within the nation's timber sector. The Group's primary operations consist of several activities in logging, kiln drying, timber moulding, wooden doors, and furniture. Besides being engaged in the upstream and downstream of timber activities, the Group is also involved in palm oil and rubber plantation and palm oil processing. One of the Group strategic thrusts is to ensure long-term profitable growth with a clearly defined business focus. The Group is better positioned to meet the challenges and opportunities in the future.